Analisis Komparasi Brand Equity Chatime dan Haus! di Kota Surabaya: Berdasarkan Jenis Kelamin dan Kelompok Usia - Aini, Luthfiyah Qurrotul; Nurhadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The food and beverage industry continue to grow rapidly, with Chatime, a Taiwanese company, and Haus, an Indonesian brand, emerging as two popular bubble tea brands consumed by many Indonesians. This study aims to examine the differences in brand equity (brand awareness, perceived quality, brand association, and brand loyalty) between these two brands, focusing on gender and age groups. A quantitative approach was employed using a survey, with a five-point Likert scale as the measurement method. The research population consists of residents of Surabaya who have previously purchased Chatime and Haus!, with a total sample of 150 respondents selected through purposive sampling. Data analysis was conducted using paired t-tests in SPSS. The results reveal significant differences in brand awareness, brand loyalty, perceived quality, and brand association between males and females, as well as among the younger age group. In contrast, for the adult age group, no significant difference was found in brand loyalty, while significant differences were observed in brand awareness, perceived quality, and brand association.